Impact of computer auditing in organizations: A bibliographical review - Lizárraga Caipo, Yerson Gabriel (2022)
Information Systems (IS) provide a unique opportunity for participating organizations to import management metrics that reflect the effectiveness of their operations. In addition to their continued competitiveness, the institutions that adopt them obtain a general advantage over those that do not adopt them, but it cannot be overlooked that information systems are a lurking risk that requires a significant investment by organizations to face up to the dangers associated with the use of this technology. The purpose of this study was to carry out a bibliographic review regarding the impact of IT audit developments in various organizations; public and private, SMEs and MSEs between 2017 and 2022. Nationally and internationally recognized databases of articles such as, Dialnet PLUS, DOAJ, SciELO, CORE, Redalyc, and Google Academic were used. The documents; categorized by date of publication, language, and country of publication; found that, conducting an IT audit had a positive impact on: risk identification, understanding of information security practices and risk management and its importance in an organization, increasing productivity, and gaining an advantage in a competitive industry